Metodo concertativo e tecniche di bilanciamento nella disciplina giuridica della libertà religiosa in tempi di emergenza (a margine delle relazioni di Silvia Baldassarre, Simone Gianello e Paolo Zicchittu) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Metodo concertativo, bilateralità e laicità - Paesi diversi, bilanciamenti simili.Concertative method and balancing techniques in the legal discipline of religious freedom in times of emergency (about the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu)ABSTRACT: In this contribution, which takes its cue from the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu, the author makes some brief considerations about the method followed - and the balancing results achieved - by the political decision-maker in the emergency management of religious freedom.